การศึกษาสภาพการดำเนินการนิเทศภายในโรงเรียนหลักสูตรสองภาษา (ไทย-จีน) ในสังกัดสำนักการศึกษา กรุงเทพมหานคร A STUDY OF THE OPERATION OF IN SCHOOL SUPERVISION IN BILINGUAL SCHOOL (THAI-CHINESE) UNDER BANGKOK METROPOLITAN ADMINISTRATION - สอดศรี, ลาวัลย์; อัครพุทธพงศ์, ปัญญา (An Online Journal of Education, 2017)
การวิจัยในครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาสภาพการดำเนินการนิเทศภายในโรงเรียนหลักสูตรสองภาษา (ไทย-จีน) ในสังกัดสำนักการศึกษากรุงเทพมหานคร ผู้ให้ข้อมูลคือ รองผู้อำนวยการฝ่ายวิชาการ หัวหน้าฝ่ายวิชาการ หัวหน้ากลุ่มสาระการเรียนรู้และครูผู้สอน จากโรงเรียนหลักสูตรสองภาษา (ไทย–จีน) ในสังกัดสำนักการศึกษากรุงเทพมหานคร 14 โรงเรียน โดยผู้ให้ข้อมูลทั้งสิ้น 112 คน เครื่องมือในการวิจัยเป็นแบบสอบถามแบบตรวจสอบรายการ (Checklist) และแบบปลายเปิด (Open ended) จำนวน 1 ฉบับ วิเคราะห์ข้อมูลโดยการแจกแจงความถี่และการหาค่าร้อยละ ผลการวิจัยพบว่า 1) ด้านการวางแผนการนิเทศภายใน มีการสำรวจสภาพปัจจุบัน ปัญหาและความต้องการ การนิเทศภายในจากครูผู้สอน โดยมีการจัดลำดับความสำคัญของข้อมูลเพื่อให้มีความสอดคล้องกับนโยบายของต้นสังกัด และกำหนดเป้าหมายทางเลือกในการปฏิบัติงานโดยความร่วมมือของผู้อำนวยการและครูผู้สอน รวมทั้งมีการแต่งตั้งคณะกรรมการดำเนินงานนิเทศภายในตามกลุ่มสาระการเรียนรู้ 2) ด้านการดำเนินการนิเทศ มีการประชุมชี้แจงเกี่ยวกับวัตถุประสงค์ของโครงการโดยผู้อำนวยการโรงเรียน มีการเลือกกิจกรรมนิเทศด้วยกิจกรรมการเยี่ยมชั้นเรียน การติดตาม การดำเนินการนิเทศภายในโดยผู้อำนวยการ สร้างขวัญและกำลังใจแก่ผู้ปฏิบัติงานด้วยการกล่าวชมเชยต่อหน้าที่ประชุม 3) ด้านการประเมินผลการนิเทศ มีการประเมินผลก่อนการปฏิบัติโดยหัวหน้ากลุ่มสาระการเรียนรู้วัดความเข้าใจของครูผู้สอนเกี่ยวกับการนิเทศภายใน ประเมินระหว่างการปฏิบัติโดยครูผู้สอนด้วยวิธีการสอบถาม และประเมินหลังการปฏิบัติ โดยผู้อำนวยการโรงเรียนและผู้รับผิดชอบโครงการโดยใช้แบบประเมินโครงการ The purpose of this research was to study the in-school supervision in bilingual schools (Thai-Chinese) under Bangkok Metropolitan Administration. The population were the Deputy Director of Academic Affairs Section, the Head of Academic Affairs Section, the Head of Learning Development Section and instructors, totaling 112 participants from 14 bilingual schools (Thai - Chinese). The research instrument was a questionnaire in checklist and open-ended format. The data was analyzed using frequency distribution and percentage. The findings revealed the following: 1) At the planning stage, there was a survey of the current condition, trouble and needs for in-school supervision from teachers. The information was prioritized to comply with the policy of original affiliation, and the operational target was defined by the cooperation of the director and teachers. Internal supervision committees were assigned in each subject area. 2) At the preparation stage, there was a meeting to clarify the purpose of the project by the director, and a classroom visit was selected as the supervision activity. The supervisory operation was followed up by the director in which good performers would be praised in the meeting for encouragement. 3) At the evaluation stage, a pre-supervision was conducted by the head of the subject area examining the instructor’s comprehension of internal supervision. The assessment during the conductive was defined by the instructors being interviewed and the post-supervision was conducted by the director and those responsible for the project using the project evaluation form.